Kualitas Fisik Daging Dada Ayam Broiler yang Didinginkan dalam Refrigerator Sebelum Penyimpanan Beku : Physical Quality of Broiler Chicken Breast Meat Cooled in The Refrigerator Before Frozen Storage - Afriani, Afriani; Angriani, Eka; Azis, Abdul (Fakultas Peternakan Universitas Jambi, 2024)
Background: Broiler chicken meat has high nutritional content that makes it susceptible to damage due to the growth and development of microorganisms, which thrive in its nutrient-rich environment. Purpose: The objective of this study aims at determining the impact of refrigerated storage duration prior to frozen storage on the physical quality of broiler chicken breast meat (pH, water binding capacity, and cooking loss). Methods: This study was conducted using a Completely Randomized Design (CRD) with 4 (four) treatments and 5 (five) replications. The research treatment was the cooling of chicken breast meat before freezing. The cooling periods were as follows: frozen without direct cooling (P0); 2 hours cooling (P1); 4 hours cooling (P2); 6 hours cooling (P3). The physical quality measurements included pH, water binding capacity, and cooking loss. The data obtained were analyzed by Analysis of Variance (ANOVA) and the results that had a significant effect were further tested by Duncan's Multiple Range Test (DMRT). Results: The refrigeration treatment had a significant impact on the pH values, water binding capacity, and cooking loss values (P<0.05). The pH values, water binding capacity, and cooking loss values were the highest in P0 (without cooling), which underwent no cooling prior to freezing. Conclusion: The duration of the refrigeration period prior to freezing had significant impacts such as a decrease in pH values, an increase in water binding capacity, and a decrease in cooking loss values of the broiler chicken breast meat. The application of a six-hour refrigeration period prior to frozen storage was observed to produce pH values, water binding capacity, and cooking loss values that remained within the range of good physical quality of broiler chicken breast meat.